The Nigeria Police Force And The Challenge Of Combating Internal Insecurity In Nigeria - Oyibokure, Goodluck Irorohwo; Okereka, Onofere Princewill; Mukoro, Akpomuvire (The Indonesian Journal of Social Studies, 2023)
This study examined the Nigeria police force and the challenge of combating internal insecurity in Nigeria. The Broken Windows Theory (BWT) was employed as the theoretical framework to guide the study. This theoretical paper draws its arguments primarily from secondary sources of data, such as existing legal frameworks and other associated policies, journal publications and textbooks. The study concluded that peace, security and safety are necessary and indispensable requirement for development and attainment of quality livelihood in society. Nigeria has recently experienced uncommon crises and feeling unsafe, each of which has resulted in the loss of lives and the destruction of property. This study recommended that State governments should be allowed by law to establish local police authority and recruits from within their communities, as opposed to posting officers and men from diverse geographical and cultural backgrounds across the country. This will go a long way toward addressing the state's unique security challenges.